Analisis Harga Pokok Produksi Dengan Metode Full Costing Pada UMKM Ayy Slime di Kota Kediri - Ro’illa Nurul Azmi; Irma Sari, Wa Ode; NURUL AZMI, RO'ILLA (Kompak :Jurnal Ilmiah Komputerisasi Akuntansi, 2025)
Because it is used to establish the product's selling price, the cost of manufacturing is a crucial figure. The cost of labor, raw materials, and manufacturing overhead must all be taken into account when compiling the cost of manufactured goods. Giving the wrong selling price is the issue Micro, Small, and Medium-Sized Businesses are facing. The full costing conduct is one of the techniques required to determine the cost of things produced in an accurate manner. Qualitative data is used in this kind of study. The cost of commodities produced at the Ayy Slime company in Kediri City is the focus of this study. The owner of the Ayy Slime company was directly interviewed for this study. According to the study's findings, the Ayy Slime company did not calculate the cost of goods produced correctly. Because of the presence of several factor, including fixed overhead costs that include uncalculated building and equipment depreciation costs, have an impact on the selling price calculation.